Modelling public bus/minibus transport accident severity in Ghana. (October 2018) - Sam, Enoch F.; Daniels, Stijn; Brijs, Kris; Brijs, Tom; Wets, Geert
Highlights: We examined factors that influence bus/minibus accident severity in Ghana. Factors are related to the driver, to road and weather conditions and to the vehicle. Additional factors are the time of the accident and the collision type. Abstract: The current safety concerns with buses/minibuses (public transport) in both developed and developing countries have warranted a renewed interest in bus/minibus safety research. Prior to this, there was a paucity of research in this domain especially in developed countries where the safety associated with buses was deemed adequate. In this study, we examined the factors that influence bus/minibus accident severity in Ghana using bus/minibus accident data from 2011–2015. We estimated the severity of bus/minibus accidents by fitting generalised ordered logit models. Our findings revealed that weekends, the absence of road median, night-time conditions, bad road terrain (curved, wet and rough roads), hit-pedestrian collisions, and drunk driving are associated with more severe bus/minibus accident outcomes. Conversely, minibuses, the absence of road shoulder, accidents in intersections, the presence of traffic control and collision types (except hit-pedestrian) are associated with less severe bus/minibus accidents.